1995
DOI: 10.1038/jcbfm.1995.97
|View full text |Cite
|
Sign up to set email alerts
|

The Role of Neuronal Nitric Oxide Synthase in Regulation of Cerebral Blood Flow in Normocapnia and Hypercapnia in Rats

Abstract: Summary:The nitric oxide synthase (NOS) inhibitors, ni tro-L-arginine, its methyl ester, and N-monomethyl-L arginine, have been shown to attenuate resting CBP and hypercapnia-induced cerebrovasodilation. Those agents nonspecific ally inhibit the endothelial and neuronal NOS (eNOS and nNOS). In the present study, we used a novel nNOS inhibitor, 7-nitroindazole (7-NI) to examine the role of nNOS in CBP during normocapnia and hypercap nia in fentanyUN20-anesthetized rats. CBP was moni tored using laser-Doppler fl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

6
68
0

Year Published

1999
1999
2019
2019

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 157 publications
(74 citation statements)
references
References 18 publications
6
68
0
Order By: Relevance
“…Furthermore, with only one exception (28), local blockade of neuronal transmission (with TTX) has not been found to alter hypercapniainduced pial arteriolar dilation (23) or hypercapnic cerebral vasodilation in general (3,42). Despite this, hypercapnia elicits a global dilation of pial arterioles, a response that is substantially diminished by selective nNOS blockade (29,37).…”
mentioning
confidence: 99%
See 2 more Smart Citations
“…Furthermore, with only one exception (28), local blockade of neuronal transmission (with TTX) has not been found to alter hypercapniainduced pial arteriolar dilation (23) or hypercapnic cerebral vasodilation in general (3,42). Despite this, hypercapnia elicits a global dilation of pial arterioles, a response that is substantially diminished by selective nNOS blockade (29,37).…”
mentioning
confidence: 99%
“…Furthermore, with only one exception (28), local blockade of neuronal transmission (with TTX) has not been found to alter hypercapniainduced pial arteriolar dilation (23) or hypercapnic cerebral vasodilation in general (3,42). Despite this, hypercapnia elicits a global dilation of pial arterioles, a response that is substantially diminished by selective nNOS blockade (29,37).Because of their unique association with neurons and pial vessels, we hypothesized, therefore, that astrocytes, via the GL, may act to transmit and amplify signals arising in comparatively few cells to the entirety of the pial arteriolar system. To that end, we determined whether injury of the GL [via topical exposure to the purported gliotoxin L-␣-aminoadipic acid (L-␣AAA)] alters hypercapnia-induced pial arteriolar dilation.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…3,4 In the cerebral circulation, neuronal and/or endothelial nitric oxide (NO) is known as the regulator of acidosisinduced dilation. [7][8][9][10] Recently, Lindauer et al 11 found that in isolated rat middle cerebral artery, denudation did not alter the vessel response to acidosis, favoring neuronal but not endothelial NO as a modulator of pH-dependent vasoreactivity in this preparation. In addition, ATP-sensitive potassium (K ATP ) channels in vascular smooth muscle have received attention as major contributors to acidosis-induced dilation in pial vessels and basilar artery.…”
mentioning
confidence: 99%
“…In contrast to the local vasomotor response to levodopa, which is likely driven by the engagement of endothelial D 1 receptors, CO 2 -mediated vasodilation is regulated downstream by the effects of nitric oxide on vascular tone (20,21). We note that, while the HC CBF response appears to be sensitive to local capillary density (see above), the vasomotor levodopa response likely is also influenced to some degree by this factor.…”
Section: Discussionmentioning
confidence: 86%